2020
DOI: 10.1002/ejp.1635
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave due to back pain, common mental disorders and disability pension: Common genetic liability

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Genetic effects are known to underlie pain, 19 CMDs, 20 22 and their mutual associations 19 , 23 25 as well as to SA 26 , 27 highlighting the need to control for familial confounding, that is, genetics and shared, mainly childhood, environmental factors in such studies. Earlier research also indicate that genetics may play a role in psychosocial working conditions 28 , 29 hence it would be important to investigate the associations between psychosocial working conditions and SA controlling for familial factors, which are available in a twin sample.…”
mentioning
confidence: 99%
“…Genetic effects are known to underlie pain, 19 CMDs, 20 22 and their mutual associations 19 , 23 25 as well as to SA 26 , 27 highlighting the need to control for familial confounding, that is, genetics and shared, mainly childhood, environmental factors in such studies. Earlier research also indicate that genetics may play a role in psychosocial working conditions 28 , 29 hence it would be important to investigate the associations between psychosocial working conditions and SA controlling for familial factors, which are available in a twin sample.…”
mentioning
confidence: 99%
“…Furthermore, we had a large working age population-based sample which enabled us to identify almost 4000 first incident SA spells due to mental diagnoses to be followed for labor market outcomes. A limitation of this study is that we had only register data and therefore lacked access to many social, health related or lifestyle factors affecting employment o sustainable working life (Dorner et al 2015;Mather et al 2020;Mather et al 2019a;Mather et al 2019b). The utilization of register data, although from multiple sources, do not completely rule out common method bias (Podsakoff et al 2012) which may have inflated our results, but one can assume that the direction of associations would be retained.…”
Section: Discussionmentioning
confidence: 96%
“…Our results based on the comparison of the whole cohort to discordant twin pairs showed the point estimates to retain the magnitude and direction, suggesting there is weak or no effect of familial confounding in the associations between SA due to various diagnosis groups and patient care. Hence this independency from familial confounding suggest direct link between SA and patient care although we expected to see familial confounding based on the genetic influence on many chronic diseases that leads to SA [25][26][27][28], but also on SA itself [9,22]. For (occupational) health care including any preventive actions for SA and/or hospitalizations in terms of inpatient-or specialized outpatient care means both tailored interventions specified by the underlying condition or diagnosis as well as monitoring SA.…”
Section: Discussionmentioning
confidence: 99%
“…SA is commonly prescribed in healthcare [8]. A lot of research have indicated that SA plays a role for many consequences, not only for disability pension (DP) [9,10], but also for mortality or even suicide [11][12][13]. However, even theoretically the effects of SA for an individual are complex and varying based on the life situation [14,15], whereas SA is also known to increase the risk of reoccurring SA, DP and unemployment [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation